2021
DOI: 10.4236/ajor.2021.115014
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Methods to Classify Real Data from Offshore Wells

Abstract: In the petroleum industry, sensor data and information are valuable. It can detect, predict and help to understand processes during oil production. Offshore wells require more attention. Once workovers, maintenance, and intervention are more costly than onshore wells. Coupling data-driven methods for well-monitoring applications, two unsupervised classification methods, one statistical and one machine learning-based, are proposed to detect anomalies in well data. The novelty is presented by applying a Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Considering R 2 , which shows the acceptable range of 99% for the best model, the suggested strategy outperforms the other two models. A study revealed the viability of the Control Chart and RF for failure detection [68]. The temporal 50,000 samples from the 3W dataset were utilized.…”
Section: Application Of Fuzzy Logic and Neuro-fuzzy Modelsmentioning
confidence: 99%
“…Considering R 2 , which shows the acceptable range of 99% for the best model, the suggested strategy outperforms the other two models. A study revealed the viability of the Control Chart and RF for failure detection [68]. The temporal 50,000 samples from the 3W dataset were utilized.…”
Section: Application Of Fuzzy Logic and Neuro-fuzzy Modelsmentioning
confidence: 99%
“…The proposed method performed better than the other two models, according to the R 2 , which was 99% for the best model. Another study revealed the viability of the Control Chart and RF for failure detection [ 73 ]. The temporal 50,000 samples from the 3W dataset were utilized.…”
Section: Predicted Analytics Models For Oandgmentioning
confidence: 99%